National Facilitators and Barriers to the Implementation of Incentives for Antibiotic Access and Innovation - Christine Årdal; Yohann Lacotte; Suzanne Edwards; Marie-Cécile Ploy; on behalf of the European Union Joint Action on Antimicrobial Resistance and Healthcare-Associated Infections (EU-JAMRAI) (MDPI AG, 2021)
Prominent reports have assessed the challenges to antibiotic innovation and recommended implementing "pull" incentives, i.e., mechanisms that give increased and predictable revenues for important, marketed antibiotics. We set out to understand countries' perceptions of these recommendations, through frank and anonymous dialogue. In 2019 and 2020, we performed in-depth interviews with national policymakers and antibiotic resistance experts in 13 countries (ten European countries and three non-European) for a total of 73 individuals in 27 separate interviews. Interviewees expressed high-level support for antibiotic incentives in 11 of 13 countries. There is recognition that new economic incentives are needed to maintain a reliable supply to essential antibiotics. However, most countries are uncertain which incentives may be appropriate for their country, which antibiotics should be included, how to implement incentives, and how much it will cost. There is a preference for a multinational incentive, so long as it is independent of national pricing, procurement, and reimbursement processes. Nine countries indicated a preference for a model that ensures access to both existing and new antibiotics, with the highest priority for existing antibiotics. Twelve of thirteen countries indicated that shortages of existing antibiotics is a serious problem. Since countries are skeptical about the public health value of many recently approved antibiotics, there is a mismatch regarding revenue expectations between policymakers and antibiotic innovators. This paper presents important considerations for the design and implementation of antibiotic pull mechanisms. We also propose a multinational model that appears to match the needs of both countries and innovators.